Pemodelan Elemen Hingga Balok Beton Bertulang Yang Diperkuat Dengan Metode Deep Embedment - Wan Muhammad Nurhud; Ridwan Ridwan; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The shear capacity of existing reinforced concrete structures is often unable to meet existing requirements. This decrease in strength can be caused by increased load, strong shear that is inadequate in initial design and material damage due to natural factors. Many methods that have been done are by means of external bonded (EB) method and near-surface mounted (NSM) method. However, shear resistance using the EB and NSM methods is prone to structural failures due to the magnification of this method only to contain an epoxy attachment and its blanket. To overcome this problem, the resistance method using deep embedment (DE) method have been proposed to reinforcement the shear capacity of existing reinforced concentrate structures. The resistance using DE method is the strenghtned shear capacity in kernel of reinforced concentrate beams. The purpose of this study was to analyze the shear behavior of reinforced concrete beams strenghtned by the DE method through finite element modeling. In this research, the existing reinforced concentrate structures put up the reinforcement by implant three kinds of steel carcass with 200 mm each gaps spread out shear beam. The maximum load result obtained from finite element analysis on reinforced concrete beams reinforced by the DE method was 31.81 kN. While the maximum deflection results obtained in finite element analysis was 8.32 mm. The failure model that occurs in the beam which is strengthened from the results of finite element analysis is the bending collapse. Keywords: shear reinforcement, deep embedement method, finite element model, shear capacity, reinforced concrete beams